A world of inequalities : Christian and Muslim perspectives : a record of the seventeenth Building Bridges Seminar - Mosher, Lucinda (Georgetown University Press, 2021)
""We agree that 'inequality' is rampant in our world; we agree less so as to whether there should be 'equality.'" So spoke a Building Bridges Seminar veteran as this project's examination of Christian and Muslim perspectives on "a world of inequalities" got underway. Founded in 2002 as an initiative of the Archbishop of Canterbury and under the stewardship of Georgetown University since 2012, the Building Bridges Seminar is believed to be the longest-running dialogue of Christian and Muslim scholar-practitioners. Meetings have been held in both Muslim- and Christian-majority locales-among them, Qatar, Singapore, Italy, and the United Kingdom. This book presents the proceedings of the seventeenth Building Bridges Seminar, convened June 18-22, 2018, in Sarajevo, Bosnia-Herzegovina"--